New Pd(ii) complexes of sulfur ylides; synthesis, X-ray characterization, a theoretical study and catalytic activity toward the Mizoroki–Heck reaction. Issue 34 (17th March 2016) - Sabounchei, S. J.; Ahmadianpoor, M.; Yousefi, A.; Hashemi, A.; Bayat, M.; Sedghi, A.; Akhlaghi Bagherjeri, F.; Gable, R. W.
Abstract : The reaction of sulfur ylides SMe2 C(H)C(O)R (R = 4-nitrophenyl, phenyl, and 3-nitrophenyl) with [PdCl2 (cod)] gives the new Pd(ii ) complexes of type cis - and trans -[PdCl2 (SMe2 C(H)C(O)R)2 ] (R = phenyl (1 ), 3-nitrophenyl (2 ), and 4-nitrophenyl (3 )). Abstract : The reaction of sulfur ylides (L) SMe2 C(H)C(O)R (R = 4-nitrophenyl, phenyl, and 3-nitrophenyl) with the dichloro(1, 5-cyclooctadiene)palladium(ii ) complex, [PdCl2 (cod)], in a 2 : 1 ratio gives the new Pd(ii ) complexes of type cis - and trans -[PdCl2 (SMe2 C(H)C(O)R)2 ] (R = phenyl (1 ), 3-nitrophenyl (2 ), and 4-nitrophenyl (3 )). Characterization of the obtained complexes was performed by elemental analysis, IR, 1 H, 13 C NMR and mass spectroscopies. Also, the structure of complex trans -[PdCl2 (SMe2 C(H)C(O)C6 H4 - p -NO2 )2 ] (3 ) was characterized by single crystal X-ray analysis. The X-ray crystallography results reveal that the structure of complex3 contains two Cα-coordinated sulfur ylide ligands in trans geometry. These air/moisture stable complexes were also employed as efficient catalysts for the Mizoroki–Heck cross-coupling reaction of several aryl halides with olefins. The coupled products of these reactions were obtained in good to excellent yields and purity, short reaction times and low catalyst loading. Also a theoretical study on the structure of the complexes1–3 have been investigated at the BP86/def2-SVP level of theory. The bonding situation between the [PdCl2 ] and L2 fragments [(Ylide)2 ] in the [L2 PdCL2 ] complexes, were carried out by NBO and energy-decomposition analysis (EDA), as well as their natural orbitals for chemical valence variation (EDA-NOCV). The results confirmed that the contribution of the electrostatic interactions in the Pd–C bond in the complexes is about 50%.